Influence of voluntary work intervention on the mood status of older volunteers - Mathew Puthenparambi, Jiby (2012)
The aim of this study was to investigate the positive and depressive mood changes in older volunteers after a three-month voluntary work intervention through a one-group experimental research design. The participants were drawn from the Volunteering, access to Outdoor activities and Wellbeing in older people (VOW) project. The participants were recently retired group, aged 50 and above (N=47, 42 female). Prior training sessions were arranged for the participants before the intervention period. Pre and post assessment of depressive mood was measured through applying the original form of Center for Epidemiologic Studies Depression Scale (CES-D) and positive mood was measure through the positive affect items of the CED-D sub-scale. Data was analyzed with descriptive statistics, paired t test, general linear model-repeated measure and multiple response frequency analysis.